Canonical lifts of cycle classes of sections - Schmidt, Johannes (Arxiv, 2016)
We present the construction of canonical lifts of l-adic cycle classes of sections of p-adic projective anabelian curves to the cohomology of arbitrary proper, regular, flat models. This answers a question of Esnault and Wittenberg.